Graphene protected Ag nanowires: blocking of surface migration for thermally stable and wide-range-wavelength transparent flexible electrodes. Issue 88 (7th September 2016) - Lee, Jaeyeong; Lee, Aram; Yu, Hak Ki
Abstract : Graphene-protected Ag nanowires have been studied for transparent flexible electrodes due to their superior thermal stability and uniform transparency. Abstract : Graphene-protected Ag nanowires have been studied for use in transparent flexible electrodes due to their superior thermal stability and uniform transparency. The protective graphene layers were synthesized via chemical vapor deposition and were transferred to both sides of spin-coated Ag nanowires. The graphene-protected Ag nanowires exhibit a stable sheet resistivity, even at 170 °C for several hundred hours, while pure Ag nanowires suffered from degradation at only 150 °C for 1 hour. The degradation model of pure Ag nanowires is suggested according to the surface diffusion kinetics, and the graphene layers were observed to block the surface plasmonic absorption of Ag nano-structures near the 350 to 400 nm range, resulting in uniform transparency at a wide range of wavelengths (300 to 1000 nm).